Biocontrol of damping off of tomato caused by Pythium aphanidermatum - and K. RAJAPPAN, S.K. MANORANTITHAM, V.PRAKASAM (Indian Phytopathology, 2002)
Damping-off of tomato caused by Pythium aphanidermatum was reduced by the application of talc based formulation of Trichoderma viride and Pseudomonas fluorescens in nursery beds before sowing. Besides reducing the pre - and post-emergence damping off these antagonists' increased the root length, shoot length and biomass production of tomato seedlings. These antagonists significantly reduced the population of P. aphanidermatum in soil.